CUEDC1 is a primary target of ERα essential for the growth of breast cancer cells. (1st November 2018) - Lopes, Rui; Korkmaz, Gozde; Revilla, Sonia Aristin; van Vliet, Romy; Nagel, Remco; Custers, Lars; Kim, Yongsoo; van Breugel, Pieter C.; Zwart, Wilbert; Moumbeini, Behzad; Manber, Zohar; Elkon, Ran; et al.
Abstract: Breast cancer is the most prevalent type of malignancy in women with ∼1.7 million new cases diagnosed annually, of which the majority express ERα (ESR1), a ligand-dependent transcription factor. Genome-wide chromatin binding maps suggest that ERα may control the expression of thousands of genes, posing a great challenge in identifying functional targets. Recently, we developed a CRISPR-Cas9 functional genetic screening approach to identify enhancers required for ERα-positive breast cancer cell proliferation. We validated several candidates, including CUTE, a putative ERα-responsive enhancer located in the first intron of CUEDC1 (CUE-domain containing protein). Here, we show that CUTE controls CUEDC1 expression, and that this interaction is essential for ERα-mediated cell proliferation. Moreover, ectopic expression of CUEDC1, but not a CUE-domain mutant, rescues the defects in CUTE activity. Finally, CUEDC1 expression correlates positively with ERα in breast cancer. Thus, CUEDC1 is a functional target gene of ERα and is required for breast cancer cell proliferation. Highlights: CUTE (CU EDC1 T ranscriptional E nhancer) is a putative ERα-responsive enhancer located in the first intron of CUEDC1 . CUTE controls CUEDC1 expression, and that this interaction is essential for ERα-mediated proliferation. Activation of CUEDC1 is essential for ERα-mediated stimulation of cellular proliferation. CUEDC1 expression correlates with ERα in breast cancer.